The method of finding extrema of functions of several variables - Jawid Hashemi; Abdulwarise Sediqy (Science and Education, 2024)
The extrema of the functions are the maximum or minimum price of the function. Each function has a graph in which we can see the maximum and minimum points and by using different methods, those points can be obtained accurately. Extrema are among the important points of the function because at these points, the function takes its maximum and minimum value. The importance of this issue is in receiving the highest or lowest price. When we consider the gasoline consumption function of Farah province, by getting the extremes of this function, we can determine how the effective factors in this function change in order to have the lowest amount of consumption and minimize this function. Similarly, any function can be considered for any problem and make it maximal or minimal. Therefore, the purpose of this research is to get the extrema of the functions so that the provisions and losses of the companies can be calculated more accurately. This research method is a phishing library and authentic scientific books have been used. As a result, every company works based on a function of several variables, after receiving its extremes, it is possible to understand how much the variables are so that the company has the most benefit and at the same time the least loss. So, the methods identified in this research to obtain the extremes of the functions of several transformations can play an effective role in improving the activities of industrial companies.